Is There a Dose–Response Relationship of Cement Volume With Cement Leakage and Pain Relief After Vertebroplasty?. Issue 4 (20th December 2016) - Fu, Zhiyi; Hu, Xiaopeng; Wu, Yujie; Zhou, Zihui
The aim of this study was to determine if there were dose–response relationships of cement volume with cement leakage and pain relief after percutaneous vertebroplasty (PVP) for osteoporosis vertebral compression fractures (OVCFs). We collected the patient and procedural characteristics on 108 patients with OVCFs in our hospital who received PVP. Univariate and multivariate analyses were performed to explore the relationships between these potential influential variables and cement leakage and pain relief at 1 month postoperatively. Multivariate linear and logistic regression analyses were conducted with the pain score reduction and the bone cement leakage as dependent variables and the potential risk factors as independent variables, respectively. The results showed that the independent risk factors for the pain relief were the cement volume injected and fracture age, and for bone cement leakage were the cement volume injected and low-viscosity cement. In conclusion, the present study indicated that there were positive dose–response correlation relationships of cement volume with the incidence of cement leakage and the degree of pain relief after PVP, respectively. Thus, the cement should be injected into the vertebrae as much as possible during the PVP procedure.